The N Terminus of Cbl-c Regulates Ubiquitin Ligase Activity by Modulating Affinity for the Ubiquitin-conjugating Enzyme - Ryan, Philip E. (American Society for Biochemistry and Molecular Biology, 2010)
Cbl proteins are ubiquitin ligases (E3s) that play a significant role in regulating tyrosine kinase signaling. There are three mammalian family members: Cbl, Cbl-b, and Cbl-c. All have a highly conserved N-terminal tyrosine kinase binding domain, a catalytic RING finger domain, and a C-terminal proline-rich domain that mediates interactions with Src homology 3 (SH3) containing proteins. Although both Cbl and Cbl-b have been studied widely, little is known about Cbl-c. Published reports have demonstrated that the N terminus of Cbl and Cbl-b have an inhibitory effect on their respective E3 activity. However, the mechanism for this inhibition is still unknown. In this study we demonstrate that the N terminus of Cbl-c, like that of Cbl and Cbl-b, inhibits the E3 activity of Cbl-c. Furthermore, we map the region responsible for the inhibition to the EF-hand and SH2 domains. Phosphorylation of a critical tyrosine (Tyr-341) in the linker region of Cbl-c by Src or a phosphomimetic mutation of this tyrosine (Y341E) is sufficient to increase the E3 activity of Cbl-c. We also demonstrate for the first time that phosphorylation of Tyr-341 or the Y341E mutation leads to a decrease in affinity for the ubiquitin-conjugating enzyme (E2), UbcH5b. The decreased affinity of the Y341E mutant Cbl-c for UbcH5b results in a more rapid turnover of bound UbcH5b coincident with the increased E3 activity. These data suggest that the N terminus of Cbl-c contributes to the binding to the E2 and that phosphorylation of Tyr-341 leads to a decrease in affinity and an increase in the E3 activity of Cbl-c.